Upaya Rehabilitasi Bagi Penyalahguna Narkotika Oleh Badan Narkotika Nasional (BNN) Kabupaten Gianyar - Haris Wirayuda; Anak Agung Sagung Laksmi Dewi; Made Minggu Widyantara (Warmadewa Press, 2022)
Drug addicts â€œsacrificeâ€ themselves because they suffer from toxidrome as a result of their own substance abuse. Article 54 of Law Number 35 of 2009 concerning Narcotics states that victims of narcotics abusers need medical or social rehabilitation. The government is tough in dealing with the problem of drug addiction through the National Narcotics Agency (BNN). This research was conducted to reveal the rehabilitation efforts for narcotics abusers by the National Narcotics Agency (BNN) of Gianyar Regency. This research was conducted using empirical legal research. The approach used in this research is a sociological approach. primary material research data sources are through field research and secondary materials written by experts and the results of scientists. The data collected were analyzed using qualitative methods. The results showed that rehabilitation assistance for drug addicts is regulated by the government in Law Number 35 of 2009 concerning Narcotics and Government Regulation Number 25 of 2011 concerning the Implementation of Compulsory Reporting of Narcotics Addicts. Rehabilitation efforts for Narcotics addicts by the National Narcotics Agency (BNN) of Gianyar Regency are to disseminate the importance of rehabilitation for narcotics addicts to agencies both government and private institutions as well as to schools in Gianyar Regency.